The Role of Organizational Citizenship Behavior in Mediating the Effect of Work-Life Balance and Job Stress on Employee Performance - Juniarti, Atty Tri; Setia, Bayu Indra; Nusantara, Bambang Dwi Aditya; Alghifari, Erik Syawal (Jambura Science of Management, 2025)
Purpose: This study aims to comprehensively examine the influence of work-life balance and job stress on employee performance, focusing on the mediating role of Organizational citizenship behavior.Design/Methodology/Approach: The data was collected by surveying 100 employees at a textile company in Bandung, Indonesia, and analyzed using Structural Equation Modeling (SEM) with Smart PLS 3.Findings: The results of this study show that work-life balance has a noteworthy influence on organizational citizenship behavior and employee performance. On the other hand, job stress only has a significant negative impact on organizational citizenship behavior, but not on employee performance. The study also demonstrates that organizational citizenship behavior has a positive and substantial effect on employee performance. Additionally, the findings suggest that organizational citizenship behavior mediates the relationship between work-life balance and job stress to employee performance.